Some urban structures of the city of Baghdad in the book almntadham Ibn al-Jawzi (d. 597 e) (Journal of the College of Education for Women, 2018)
We conclude that this study has dealt with an important aspect of the book that was not clearly defined in the book as it was derived through the book's translations, namely, the extraction of those urban structures of the city of Baghdad, which were of great importance in the religious, cultural, economic and social life at that time, The important link that reflected the development of the Islamic city in general and Baghdad in particular, as he addressed such urban facilities through the translations of the book that did not offer the outline or information about those facilities, but only the name only, and here lies the difficulty in addressing Such as T. As subjects because they need the most accurate analysis of facilities through the budget with other sources of direction, and we find like this when most of Margena who cite passing references to such facilities at the level of the city or the country, and this is part of their curriculum in this area